Odpowiedzi

2009-12-19T22:05:01+01:00
{2-[(3*5)-70:4-2]-2+24*3}:4=(2-(15-70:4-2)-2+24x3):4=
(2-(15-17,5-2)-2+72):4=(2-(15-17,5-2)-2+72):4=(2-(-5,5)-2+72):4=19,375
2009-12-19T22:08:28+01:00
(-2(15-17,5-2)-2+24×3):4
(-2×(-4,5)-2+24×3):4
(9-2+24×3):4
(7+72):4
79:4
19,75
Najlepsza Odpowiedź!
2009-12-20T00:49:07+01:00
(2 - ([3 x 5] - 70 : 4 - 2) - 2 + 24 x 3) : 4 =
(2 - (15 - 70 : 4 - 2) - 2 + 24 x 3) : 4 =
(2 - (15 - 17.5 - 2) - 2 + 24 x 3 ) : 4 =
(2 - (-2.5 - 2) - 2 + 24 x 3) : 4 =
(2 - (-4.5) - 2 + 24 x 3) : 4 =
(2 - (-4.5) - 2 + 72) : 4 =
(6.5 - 2 + 72) : 4=
(4.5 + 72) : 4 =
76.5 : 4 = 19.125